A cardiac rehabilitation program to enhance the outcomes of older women with heart disease : development of the Group Rehabilitation for Older Women (Grow) Program - Hancock, K.; Daly, J.; Cockburn, J.; Davidson, Patricia; Moser, D.; Goldston, K.; Elliott, D.; Webster, J.; Speerin, R.; Wade, V.; Clarke, M.; Anderson, M.; et al. (Australian Rehabilitation Nurses' Association, 2003)
Background: Heart disease in older women commonly manifests as acute coronary syndromes (unstable angina pectoris, or acute myocardial infarction) and heart failure (HF). These conditions are major causes of morbidity and mortality in Australia and internationally. Following an acute cardiac event, women have poorer outcomes including higher mortality rates, and incidence of complications together with greater psychological morbidity compared with men. Traditionally cardiac rehabilitation programs have not specifically targeted the needs of older women. Aim: To document the systematic development processes of a nurse-facilitated intervention to improve the outcomes of older women with heart disease. Method: A critical literature review, supported by consumer and key informant consultation, was undertaken to develop an interactive program focussing on the use of goal setting, provision of information, and use of cognitive behavioural strategies in older women. Findings: On the basis of the critical literature review, consumer consultation and key informant workshops, the research team concluded that the key strategies to be incorporated in the 8 week evidence-based, secondary prevention intervention (GROW program) are: (1) provision of succinct and clear information to participants; (2) facilitation of group interaction; (3) establishment of guidelines for referral to experts for management of anxiety, depression, complex social issues and clinical deterioration; (4) minimisation of participant burden with evaluation across the care continuum; (5) facilitation of self-care strategies; (7) an emphasis on cognitive-behavioural strategies to enhance self-management; in particular communication and strategies to promote self-efficacy; and (8) information, support and resources to assist nurses in facilitating the intervention. Conclusion: It would appear from a critical literature review, consultation with consumers and clinical experts that an intervention focusing on psychosocial morbidity but also improve risk factor adherence and secondary prevention strategies.